Compulsive gabapentin abuse despite lack of desirable effects: A case report. (2nd November 2017) - Banker, Kelly; Ruekert, Laura; Hasan, Syed
ABSTRACT: Gabapentin is a federally non-scheduled anticonvulsant used in clinical practice for several neuropsychiatric conditions. Reports of abuse and descriptions of desirable effects experienced by users are frequent in the literature. The following case reports a patient with compulsive gabapentin abuse despite a lack of previously described desirable effects.